Spatial variability of physical attributes of a cohesive soil under conventional and no-tillage management systems - Ribeiro, Letícia da Silva; Oliveira, Ismênia Ribeiro de; Dantas, Jussara Silva; Silva, Camila Vieira da; Silva, Grazieli Brito da; Azevedo, James Ribeiro de (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the spatial variability of moisture content, bulk density,and porosity of a cohesive soil under conventional and no-tillage management systems. Two regular grids were installed, one for each management type. The soil was collected at the 0.00–0.20-m depth and the spatial variability of its attributes was analyzed by semivariogram parameters and ordinary kriging geostatistical interpolation. The soil showed greater bulk density and moisture conservation under no-tillage, and greater porosity under conventional tillage.